Radiation Recall Pneumonitis Induced by Anti-PD-1 Blockade: A Case Report and Review of the Literature - Chen, Yu; Huang, Zhaoqin; Xing, Ligang; Meng, Xiangjiao; Yu, Jinming (Frontiers in Oncology, 2020)
Background: Radiation recall pneumonitis (RRP) is an unpredictable but relatively severe subclinical radiation damage which occurs in the previously irradiated fields of pulmonary tissue after administration of a systemic agent. Previous reports of RRP were mainly attributed to chemotherapy and molecular-target agents. RRP induced by immunotherapy has been rarely reported. Here we describe a case of a novel pattern of RRP induced by anti-PD-1 blockade Camrelizumab two years after radiotherapy, with some focus on further understanding of this phenomenon. Case Report: A 64-year-old man with non-small cell lung cancer (NSCLC) received two cycles of chemotherapy with cisplatin and pemetrexed first. Subsequently, he underwent concomitant chemoradiotherapy with cisplatin and pemetrexed to simultaneous integrated boost (SIB) radiotherapy. After fifteen months, due to tumor progression and brain metastasis, he started with administration of anti-PD-1 blockade Camrelizumab (200mg q2w) and stereotactic radiosurgery (SRS). The patient developed fever, dyspnea and cough after the eighth administration of Camrelizumab. Meanwhile, his chest CT revealed patchy consolidation and ground-glass opacities localized within the previously irradiated area. Subsequent treatment regimen was adjusted to 80mg q12h predinisolone with discontinuation of Camrelizumab. Then the symptoms gradually eased and reexamination of CT showed significant improvement in RRP after two weeks. Conclusion: Our case report presents a novel pattern of RRP induced by anti-PD-1 blockade Camrelizumab two years after radiotherapy. This indicates that previous radiotherapy combined with subsequent anti-PD-1 blockade has a potential to cause overlapping damage to lung, suggesting that intensive attention might be needed for patients who are treated with anti-PD-1 blockade in conjunction with a prior history of thoracic radiation.